Coefficient Estimates for Certain Subclasses of Analytic Functions of Complex Order (European Journal of Pure and Applied Mathematics, 2017)
In this document, we introduce and investigate two interestingsubclasses $\mathcal{H}_{g}$(n,b,$λ,α,δ$) and$\mathcal{H}_{g}$(n,b,$λ,α,δ;μ$) of analyticfunctions of complex order in the open unit disk U, which aredefined by means of the familiar multipliter operator. Forfunctions belonging to the each of these subclasses, we obtainserveral results involving (for example) cofficient bounds. Theresults presented here would generalize many known results.